Succession of the wheat seed-associated microbiome as affected by soil fertility level and introduction of Penicillium and Bacillus inoculants in the field - Nunes, Inês; Hansen, Veronika; Bak, Frederik; Bonnichsen, Lise; Su, Jianqiang; Hao, Xiuli; Raymond, Nelly Sophie; Nicolaisen, Mette Haubjerg; Jensen, Lars Stoumann; Nybroe, Ole (FEMS microbiology ecology, 2022)
Abstract During germination, the seed releases nutrient-rich exudates into the spermosphere, thereby fostering competition between resident microorganisms. However, insight into the composition and temporal dynamics of seed-associated bacterial communities under field conditions is currently lacking. This field study determined the temporal changes from 11 to 31 days after sowing in the composition of seed-associated bacterial communities of winter wheat as affected by long-term soil fertilization history, and by introduction of the plant growth-promoting microbial inoculants Penicillium bilaiae and Bacillus simplex. The temporal dynamics were the most important factor affecting the composition of the seed-associated communities. An increase in the relative abundance of genes involved in organic nitrogen metabolism (ureC and gdhA), and in ammonium oxidation (amoA), suggested increased mineralization of plant-derived nitrogen compounds over time. Dynamics of the phosphorus cycling genes ppt, ppx and cphy indicated inorganic phosphorus and polyphosphate cycling, as well as phytate hydrolysis by the seed-associated bacteria early after germination. Later, an increase in genes for utilization of organic phosphorus sources (phoD, phoX and phnK) indicated phosphorus limitation. The results indicate that community temporal dynamics are partly driven by changed availability of major nutrients, and reveal no functional consequences of the added inoculants during seed germination. Development of the wheat seed-associated microbiome and its functional potential of nitrogen and phosphorous cycling.